Implications for design-focused professional doctorates of Australian research into professional doctorates - Love, Terence (University of Tsukuba, 2003)
Australia is a forerunner in professional doctoral education and in research aimed at improving professional doctorates. This is reflected in the last decade of Australian Biennial Professional doctoral conferences, and the significant research funding support by the Australian Research Council aimed at identifying best practices in professional doctoral education.This paper draws out the implications for design-focused professional doctorates in design disciplines of the findings from two substantial government-funded research projects into the broad range of professional doctorates currently available in Australia, and the papers of the 2002 Australian Biennial Professional Doctorate conference.